Nutritional requirement of groundnut (Arachis hypogaea L.) CV. TG-3 in red soils of Kerala - Mathew Joseph (Department of Agronomy, College of Agriculture, 1990)
A field experiment was conducted at the College of Agriculture, Vellayani during 1989 to study the influence of three levels of each nitrogen (0.10 and 20 kg/ha), phosphorus (0.50 and 100 kg/ha) and potassium (0.50 and 100 kg/ha) on growth, yield and uptake of major nutrients in groundnut cv. Tg-3 under open upland conditions. The trial was conducted as 33 +1 partially confounded factorial experiment in Randomised Block Design with two replications. Higher levels of nitrogen had profound influence on growth characters like plant height and number of branches per plant. But the effect was negative in the case of number of root nodules per plant. Higher levels of phosphorus significantly influenced plant height, number of branches and LAI. Potassium had significant influence only on plant height and leaf area index. Yield attributes like number of pods and weight of pods per plant were not influenced significantly by the main or the interaction effects of the major nutrients. However the fertilizer treatments registered a higher value than the control plots. Application of 20 kg N/ha significantly increased the weight of kernel per plant, number of pops and 100 kernel weight. The number of pops was found to increase with higher levels of phosphorus (100 kg P2O5/ha). The maximum harvest index and pod yield per hectare was recorded by 10 kg N/ha. Potassium significant influence on bhusa yield at 100 kg K2O/ha. However the application of 20 kg N/ha, 50 kg P2O5/ha and 100 kg K2O/ha recorded the maximum pod yield. The response of groundnut to nitrogen levels was quadratic and that to potassium levels was linear. The DMP was significantly influence by the application of potassium only at 100 kg K2O/ha. The oil content of kernel was found to be unaffected by the main or their intraction effects of nitrogen, phosphorus and potassium. The protein content was significantly increased with 20 kg N, 50 kg P2O5 and 100 kg K2O/ha. The nitrogen uptake by the crop was maximum at 20 kg N and at 100 kg K2O/ha. The levels of P significantly influenced the phosphorus uptake by the crop and it was maximum with 100 kg P2O5/ha. A potassium level of 50 kg K2/ha registered the maximum P uptake by the crop. The potassium uptake by the crop was significantly influenced by the application of potassium at 100 kg K2O/ha. The study indicated that application of 20 kgN, 50 kgP2O5 and 100kg K2O per hectare recorded the maximum pod yield and net returns from groundnut cv. TG-3 under open gardenland conditions in the red loam soils of Vellayani.